2018
DOI: 10.3390/app8112053
|View full text |Cite
|
Sign up to set email alerts
|

An Optimization Framework for Wind Farm Design in Complex Terrain

Abstract: Designing wind farms in complex terrain is an important task, especially for countries with a large portion of complex terrain territory. To tackle this task, an optimization framework is developed in this study, which combines the solution from a wind resource assessment tool, an engineering wake model adapted for complex terrain, and an advanced wind farm layout optimization algorithm. Various realistic constraints are modelled and considered, such as the inclusive and exclusive boundaries, minimal distances… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…This model was first used in an idealized layout optimization problem, i.e., a wind farm with 25 turbines on a Gaussian 2D hill [33]. Recently, it was also employed in a more realistic optimization framework and tested on the design optimization of a real wind farm in complex terrain [34], which is, in fact, the same wind farm as described in Section 2. Random search algorithm, a metaheuristic algorithm developed specifically for wind farm layout optimization in [19], was used in this framework.…”
Section: Wake Modellingmentioning
confidence: 99%
See 1 more Smart Citation
“…This model was first used in an idealized layout optimization problem, i.e., a wind farm with 25 turbines on a Gaussian 2D hill [33]. Recently, it was also employed in a more realistic optimization framework and tested on the design optimization of a real wind farm in complex terrain [34], which is, in fact, the same wind farm as described in Section 2. Random search algorithm, a metaheuristic algorithm developed specifically for wind farm layout optimization in [19], was used in this framework.…”
Section: Wake Modellingmentioning
confidence: 99%
“…An adapted Jensen wake model was proposed by Feng and Shen for wind farms in complex terrain and applied in the layout optimization of a wind farm on a 2D Gaussian hill [33]. This wake model was later adopted in a design optimization framework that can consider real wind farms in complex terrain and tested on a wind farm with 25 turbines at a real complex terrain site [34]. Kuo et al [35] solved the layout optimization problem for wind farms in complex terrain by coupling computational fluid dynamics (CFD) with mixed-integer programming (MIP), in which the wake effects were approximated by CFD simulations iteratively.…”
Section: Introductionmentioning
confidence: 99%
“…These circles are situated in threedimensional space, where the heights depend on the terrain elevations, 𝐸 1 and 𝐸 2 , and the hub heights of the respective turbines, 𝐻 1 and 𝐻 2 , at points 𝑃 1 and 𝑃 2 , respectively. This suggests a "complex terrain" (i.e., various elevations), as tackled by Feng et al [49]. We simplify in terms of the downstream wind flow and assume that 𝑃 1 = (𝑥 1 , 𝑦 1 , 𝑧 1 ) 𝑇 with 𝑧 1 = 𝐸 1 + 𝐻 1 and 𝑃 2 = (𝑥 2 , 𝑦 2 , 𝑧 2 ) 𝑇 with 𝑧 2 = 𝐸 2 + 𝐻 2 .…”
Section: Wake Asymmetric Thrust Loadmentioning
confidence: 99%
“…Sessarego et al [16] simulated wind turbine/farm flows in complex terrain using both Reynolds averaged Navier-Stokes with an actuator disc model and large eddy simulation with actuator line model and results were compared with detailed field measurements from two met-masts and SCADA (supervisory control and data acquisition) data. Feng et al [17] developed an optimization framework for wind farm layout optimization in complex terrain, which employs a CFD (Computational Fluid Dynamics) wind resource assessment tool, an engineering wake model adapted in complex terrain and an advanced wind farm layout optimization algorithm, and it was found that the framework can provide a better layout than the original layout.…”
Section: Current Status In Wind Turbine Aerodynamicsmentioning
confidence: 99%